The diagnostic role of resting myocardial blood flow in STEMI patients after revascularization - Yan, Ming; Shang, Hua; Guo, Xiaorui; Hao, Luping; Hou, Shuang; Zheng, Hongming (Frontiers in Cardiovascular Medicine, 2024)
Background The value of semiquantitative resting myocardial perfusion imaging (MPI) in coronary artery disease (CAD) is limited. At present, quantitative MPI can be performed by a new cadmium zinc tellurium single-photon emission computed tomography (CZT-SPECT) scan. The quantitative index of resting myocardial blood flow (MBF) has received little attention, and its manifestations and clinical value in the presence of unstable coronary blood flow have not been clarified. Purpose In patients with ST-segment elevation myocardial infarction (STEMI), whether resting MBF can provide additional value of blood flow than semi-quantitative resting MPI is not sure. We also explored the influencing factors of resting MBF. Methods This was a retrospective clinical study. We included 75 patients with STEMI in the subacute phase who underwent resting MPI and dynamic scans after reperfusion therapy. General patient information, STEMI-related data, MPI, gated MPI (G-MPI), and resting MBF data were collected and recorded. According to the clinically provided culprit vessels, the resting MBF was divided into ischemic MBF and non-ischemic MBF. The paired Wilcoxon signed-rank test was used for resting MBF. The receiver operating characteristic (ROC) curves were used to determine the optimal threshold for ischemia, and multiple linear regression analysis was used to analyze the influencing factors of resting MBF. Results There was a statistically significant difference between the ischemic MBF and non-ischemic MBF [0.59 (0.47–0.72) vs. 0.76 (0.64–0.93), p < 0.0001]. The ROC curve analysis revealed that resting MBF could identify ischemia to a certain extent, with a cutoff value of 0.5975, area under the curve (AUC) = 0.666, sensitivity = 55.8%, and specificity = 68.7%. Male sex and summed rest score (SRS) were influencing factors for resting MBF. Conclusion To a certain extent, resting MBF can suggest residual ischemia after reperfusion therapy in patients with STEMI. There was a negative correlation between male sex, SRS, and ischemic MBF. A lower resting MBF may be associated with more severe myocardial ischemia.